Management of Storage Pathogens of Cereal Grains: A Review - Alokesh Das; Subrata Mandal; Sudipa Nag; Bholanath Mondal (International Journal of Economic Plants)
Storage is the cultural process of preserving grains because grains were stored after harvesting and till manufactured to the factory or consumer directly. There were many pathogens (like bacteria, fungi, yeast etc.) playing a significant role in infecting grain and destroying the grains partly or completely. Many remedies used for solving this problem are insufficient. Among the phytopathogens, fungi have devastating power to destroy plants by its mycelium. Fungi can infect seeds through generation after generation and trouble in the storage process. Different microorganisms produce different types of myco-toxins within the cereal grains in the storage and cause the loss of food value. Several techniques are available to determine the factor affecting store grain cereals. Many cultural and conventional established techniques were applied to overcome the loss of grains during storage. In this regard, drying in different ways is effective. In recent years, the convention of storage techniques for cereal grains has evolved with the help of hermetic storage, aeration, updated atmospheric storage and refrigerated storages. Mainly, three grains from cereals i.e. rice, wheat, maize were taken into consideration for this review and only fungal pathogens of stored grains and their modern agriculture remedies are discussed.